The social effects of the legislative omission: دراسة مقارنة - طالب حيدر; حارث سرى (Journal of Legal Sciences, 2019)
The effectiveness and quality of legislation depends on the extent to which they respond to the political, social, economic and moral reality. The quality of the legislation is not limited to professional drafting, accuracy, clarity, comprehensiveness, accessibility and understanding, but also depends on the reality of this legislation and its acceptance and application by those who are addressed to them. Therefore, any shortage or deficiency in these legislations would make these laws separate from the reality and enter into the circle of legislative alienation. In this study, we tried to focus on the social effects of the legislator’s failure to organize all the necessary aspects of the effectiveness of rights or liberties subject of organization and the vacuum that may result from this omission of legislative that weaken the constitutional guarantees prescribed for the exercise of these rights and enjoyment of these freedoms and the effect of this omission Legal centers and legal relations in the community and stability Good laws are those laws that achieve social justice and the stability of centers and social relations for a reasonable time with the possibility of legitimate expectation of any changes or amendments that can affect this legislation, here, the role of oversight of legislative omission exercised by the constitutional judiciary in dealing with the text appears, the legislative limitations, and the structure of the legislative authority shows the omissions and lack of organization to avoid them and reduce their social impact.